The influence of green product development performance to enhance enterprise effectiveness and innovation - Nguyen Trong Luan; Doan Nguyen Duy Hau; Nguyen Thi Anh Thu (Economies, 2022)
Climate change and environmental crises are currently affecting the living environment of both people and the planet in general. This necessitates businesses to have a prompt and effective response to minimize or improve the harmful effects that lead to environmental imbalance and fulfill corporate social responsibility through focusing on transitioning to a model of sustainable economic development and encouraging the development and production of green products. This study discovers that the five factors green creativity, green dynamic capabilities, green transformational leadership, reactive green innovation, and proactive green innovation have a positive influence on and aid in the creation of exceptional green product development performance. A survey questionnaire was used to collect data for this research with the participation of more than 1000 people. These figures reveal that the participants are people who are knowledgeable about environmental issues and are actively interested in environmental protection (as well as people who have used green products). Research using software to support SPSS.20 and AMOS.24 to test the hypotheses. The study serves as a framework to help businesses better comprehend the relationship between economics and the environment with the purpose of providing valuable data and raising awareness for innovation in development models for businesses and organizations.
Keywords: 330; green creativity; green dynamic capabilities; green product development performance; green transformational leadership; proactive green innovation; reactive green innovation